Physician perceptions of electronic medical records: the impact of system service quality, and generation/experience gaps. (6th February 2020) - Hung, Shin-Yuan; Nakayama, Makoto; Chen, Charlie C.; Tsai, Fang-Lan
Electronic medical record (EMR) systems are complex, organisational-wide information systems involving stakeholders in various medical fields and responsibilities. Assessing the usefulness of EMR, therefore, is not straightforward. Using SERVQUAL, this study assesses the relationship between perceived EMR service quality and the perceived usefulness (subjective belief), expectation (judgment), and satisfaction (affect) of EMR systems. Data were obtained from 338 physicians in ten medical centres and 15 regional hospitals in Taiwan. The results show that physicians' perceived EMR service quality has a much stronger effect on non-affect outcomes than on an affect-based antecedent like satisfaction. Due to the complexity of EMRs, a beneficial assessment of EMRs requires the clinical experience of individual physicians and organisational perspective on how EMRs facilitate their tasks.